Flavonoid-rich extract of Parquetina nigrescens prevents intestinal ischemia-reperfusion injury in Wistar rats via modulation of inflammatory cytokines and antioxidant defense (2018)
The search for relatively safe and cost-effective strategies at minimizing tissue damage following acute inflammatory bowel conditions still continues. To further explore the mechanisms of protection by Parquetina nigrescens in gut ischemia-reperfusion injury, the present study sought to investigate the effects of the flavonoid-rich extracts of Parquetinanigrescens (FPN) on serum levels of inflammatory cytokines (TNF-alpha and IL-lbeta), the oxidant-antioxidant status, as well as the morphology of the intestinal mucosa in a rat model of ischemia-reperfusion injury. Thirty six male Wistar rats were randomly allocated into 6 groups with the sham-operated group subjected to laparotomy only. In the ischaemia-reperfusion (IR) group, the superior mesenteric artery (SMA) was occluded for 45 minutes, followed by reperfusion for another 45 minutes. Other groups had ischemic pre-conditioning (IP), melatonin (10 mg/kg), FPN1 (250 mg/kg) or FPN2 (500 mg/kg) before IR. Serum cytokine levels were determined, histopathological examination and biochemical analyses of small intestines were carried out. IR produced significant increases (p<0.05) in MDA and TNF-alpha with significant reductions (p<0.05) in GSH, GPx and SOD. FPN2 produced the best am elioration of effects of IR injury on M DA, H20 2, GSH and SOD, as well as the best preservation o f m ucosal integrity at histology. The increased TNF - alpha level was, however, best ameliorated with ischemic preconditioning. Our results provide evidence for the amelioration of IR injury by flavonoids derived from Parquetinanigrescens via anti-inflammatory effects, mainly involving TNF-alpha reduction. This effect was also positively con-elated with reduction in oxidative damage.